Positioning One-Self as Leader Through a Speech: Mood and Modality Analysis - Wahyu Permana; Elysa Hartati (The Doctoral Studies Program of Linguistics of Udayana University, 2024)
Fighting fascism was shown by Charlie Chaplin in his speech in The Great Dictator film. Thus, this research aimed to reveal Chaplin's Point of View, attitudes, and judgments toward people through mood and modality analysis in his speech. The-descriptive qualitative method and Hallidayan SFL theory were used to analyze the speech. The findings revealed that Chaplin used 81% declarative and 19% imperative from 54 clauses. Chaplin did not use interrogatives in the speech to encourage people to fight fascism. Furthermore, the researchers found that Chaplin mostly used 92% modalization probability to describe a wonderful future if the dictator loses. Furthermore, Chaplin used an 8% modulation obligation to depict an action that Chaplin should take. Based on the data, it could be interpreted that Chaplin's position was higher than the audiences. He viewed his audience as being weak. Chaplin calls on the soldiers to stop being the slaves of dictators and refuse to listen to their orders. This study from the speech could provide information for people interested in mood and modality and the meaning of the speech related to the Russia-Ukraine war.